The expansion of heterochromatin blocks in rye reflects the co-amplification of tandem repeats and adjacent transposable elements - Evtushenko, E V; Levitsky, V G; Elisafenko, E A; Gunbin, K V; Belousov, A I; Šafář, J; Doležel, J; Vershinin, A V (BMC genomics, 2016)
BACKGROUND: A prominent and distinctive feature of the rye (Secale cereale) chromosomes is the presence of massive blocks of subtelomeric heterochromatin, the size of which is correlated with the copy number of tandem arrays. The rapidity with which these regions have formed over the period of speciation remains unexplained. RESULTS: Using a BAC library created from the short arm telosome of rye chromosome 1R we uncovered numerous arrays of the pSc200 and pSc250 tandem repeat families which are concentrated in subtelomeric heterochromatin and identified the adjacent DNA sequences. The arrays show significant heterogeneity in monomer organization. 454 reads were used to gain a representation of the expansion of these tandem repeats across the whole rye genome. The presence of multiple, relatively short monomer arrays, coupled with the mainly star-like topology of the monomer phylogenetic trees, was taken as indicative of a rapid expansion of the pSc200 and pSc250 arrays. The evolution of subtelomeric heterochromatin appears to have included a significant contribution of illegitimate recombination. The composition of transposable elements (TEs) within the regions flanking the pSc200 and pSc250 arrays differed markedly from that in the genome a whole. Solo-LTRs were strongly enriched, suggestive of a history of active ectopic exchange. Several DNA motifs were over-represented within the LTR sequences. CONCLUSION: The large blocks of subtelomeric heterochromatin have arisen from the combined activity of TEs and the expansion of the tandem repeats. The expansion was likely based on a highly complex network of recombination mechanisms.
Keywords: tandemové repetitivní sekvence; Heterochromatin; Phylogeny; Chromosomes, Plant; žito; Oligonucleotide Array Sequence Analysis; Sequence Analysis, DNA; In Situ Hybridization, Fluorescence; Tandem Repeat Sequences; amplifikace genu; Rye; TE–tandem junctions; Secale; transpozibilní elementy DNA; sekvenční analýza DNA; DNA motifs; Gene Amplification; Subtelomeric heterochromatin; Transposable elements; hybridizace in situ fluorescenční; komponenty genomu; fylogeneze; Genome Components; Secale cereale; sekvenční analýza hybridizací s uspořádaným souborem oligonukleotidů; DNA Transposable Elements; 1RS BAC library; heterochromatin; Chromosomes, Artificial, Bacterial; Tandem repeats; chromozomy rostlin; 454 sequences; umělé bakteriální chromozomy; genová knihovna; Gene Library